EFFECTIVE THEORY FOR BINARY STARS AND ITS APPLICATION TO GRAVITATIONAL WAVES - Canazas Garay, Anthonny Freddy (2015)
The recent detections of gravitational waves have brought renewed attention to the problem of obtaining high accuracy predictions for the gravitational radiation spectra emitted by binary systems with black holes or neutron stars constituents. This work explains how effective field theory applied to gravitation can be used to describe a gravitationally interacting extended object as in the binary system case. Gravitational wave emission from the binary system is shown by using methods that are usually applied in quantum field theory.